Manajemen Pembinaan Keterampilan Berfikir Tingkat Tinggi untuk Meningkatkan Prestasi Siswa di Bidang Eksakta - Tuti Alawiyah; Sutisna Sutisna; Mohammad Dzakiyyuddin (Journal of Elementary School (JOES), 2023)
This research aims to reveal and analyze the management of high-level thinking skills training at SMAN 2 Cirebon City for achievements in the exact sciences field. Consist of planning stage, implementation methods, handling obstacles, to the extent to which the results of this coaching can be seen from the achievements achieved by the participants. The research method used is a qualitative research method in case study, and uses a descriptive analysis approach. Data was collected through in-depth interviews, observation and documentation studies. The planning phase begins with a program meeting, forming a committee, determining activities and facilities, designing a calendar, compiling monitoring instruments and a mechanism for measuring coaching results. Implementation process begins with program promotion and participant recruitment. Thinking skills training focuses on knowledge transfer abilities, critical and creative thinking, and problem solving. Field constraints are acted upon by the vice principal in charge of quality improvement, while in coordination with the school principal. No serious obstacles were found that interfered with activity management. Internal improvements are carried out by evaluating improvements to operational standards and controlled quality standards for continuous internal quality assurance. The main result of this coaching is that the students' achievements are quite satisfactory because they have achieved achievements in the field of exact sciences up to the national level. Keywords: Training Management, Higher Order Thinking Skills, Student Achievement, Math And Science